2018
DOI: 10.1186/s11658-018-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive effect of co-inhibiting PD-1 and CTLA-4 expression on H22 hepatomas in mice

Abstract: ObjectiveWe investigated the suppressive effect of siRNA-mediated co-inhibition of PD-1 and CTLA-4 expression on H22 hepatomas in mice.MethodsMurine H22 cells were cultured in vivo in ICR mice. An allograft tumor model was also established in another ICR mouse group. The tumor-bearing mice were randomly divided into four groups: control, single PD-1 siRNA, single CTLA-4 siRNA, and double PD-1 + CTLA-4 siRNAs. The survival time and physiological condition of the mice were observed after the injection of the siR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…В исследованиях с использованием изолированных островков поджелудочный железы человека показано, что воздействие стрессовых факторов (гипергликемия, избыточное количество свободных радикалов, активные формы кислорода, продукция IL-1β клетками микроокружения) усиливает экспрессию Fas на β-клетках, что приводит к их гибели по механизму Fas-опосредованного апоптоза [18]. Иммунокомпетентные клетки, инфильтрирующие островковую ткань поджелудочный железы, продуцируют провоспалительные цитокины: интерлейкин 1b (IL-1b), фактор некроза опухолей α (TNF-a) и интерферон g (IFN-g), известные своими проапоптогенными свойствами [16,19,20]. IL-1β индуцирует усиление экспрессии Fas на β-клетках, что повышает их готовность к Fas-опосредованному апоптозу, который реализуется аутореактивными Т-клетками, экспрессирующими FasL.…”
Section: Introductionunclassified
“…В исследованиях с использованием изолированных островков поджелудочный железы человека показано, что воздействие стрессовых факторов (гипергликемия, избыточное количество свободных радикалов, активные формы кислорода, продукция IL-1β клетками микроокружения) усиливает экспрессию Fas на β-клетках, что приводит к их гибели по механизму Fas-опосредованного апоптоза [18]. Иммунокомпетентные клетки, инфильтрирующие островковую ткань поджелудочный железы, продуцируют провоспалительные цитокины: интерлейкин 1b (IL-1b), фактор некроза опухолей α (TNF-a) и интерферон g (IFN-g), известные своими проапоптогенными свойствами [16,19,20]. IL-1β индуцирует усиление экспрессии Fas на β-клетках, что повышает их готовность к Fas-опосредованному апоптозу, который реализуется аутореактивными Т-клетками, экспрессирующими FasL.…”
Section: Introductionunclassified
“…The early-stage transplantation model was mainly based on the transplantation with the same gene strain tumor cells on homologous mice. Transplanted H22 cells into BALB/C mice ( 78 ) or Hepa1-6 cells into C57 mice ( 79 ) subcutaneously or in situ could be constructed as a mouse resource HCC model. Subcutaneous tumors are easier to be observed and monitored, and in situ tumors mimic the local environment better ( 80 ).…”
Section: Hepatocellular Carcinoma Transplantation Mouse Modelsmentioning
confidence: 99%
“…siRNA against PD-L1 can preferentially transfer CD11c+ PD-L1+ tolerogenic DCs into potent stimulators of CTLs in TMEs through PD-L1 downregulation and multiple TLRs activation ( 119 ). The antitumor efficacy of siRNA against PD-L1 can be enhanced by co-inhibiting with CTLA-4 ( 120 ). Another study also indicated that siRNA against PD-L1 or PD-L1 improved effector functions of tumor-specific CD4+ and CD8+ T cells in vitro ( 121 ), suggesting that PD-L1/PD-L2 siRNA is an exciting strategy to inhibit the immune suppressive tumor-specific T cells.…”
Section: Small Molecule-based Immune Activationmentioning
confidence: 99%